Occurrence and biodiversity of cyst nematodes in wheat and barley cultivation areas of Uşak Province, Türkiye - Türkay, Selin; Yüksel, Ebubekir; Bozbuga, Refik; Dinçer, Dilek; Ocal, Atilla; Ulaş, Furkan; Sameeullah, Muhammad; Dababat, Abdelfattah A.; Imren, Mustafa (TÜBİTAK, 2024)
Plant parasitic nematodes (PPNs) are one of the major threats to various crops including cereals. In wheat and barley production, the profitability of cultivation heavily depends on the management of cyst nematodes (CNs), especially on Heterodera avenae, H. filipjevi, and H. latipons. In this study, field surveys were conducted in wheat and barley cultivation systems of Uşak Province to reveal the presence and diversity of PPNs. In total, 80 wheat and barley fields were surveyed, and samples (soil and root) were processed for the isolation and identification of PPNs. The PPN genera were identified to the species level based on morphological and morphometric characters. CNs were further analyzed using molecular methods. In total, 17 species belonging to 10 genera were identified. Helicotylenchus Steiner, Pratylenchoides Winslow, Merlinius Siddiqi, and Heterodera Schmidt were the most prevalent and abundant genera. The Shannon diversity index averaged at 2.51 in the wheat and barley fields, indicating a moderate level of biodiversity. The evenness value of 0.798 suggests a high degree of uniformity among migratory PPNs. The results indicate that PPNs have a serious impact on reducing grain yield and quality in the wheat- and barley-growing areas of Uşak Province.